2006
DOI: 10.4319/lo.2006.51.1_part_2.0702
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in the areal hypolimnetic oxygen deficit (AHOD) of Onondaga Lake: Evidence of sediment feedback

Abstract: Long-term trends in the rate of depletion of hypolimnetic dissolved oxygen (DO) are documented for ionically enriched hypereutrophic Onondaga Lake, New York, for the 1978-2002 interval. Depletion rates, represented as areal hypolimnetic oxygen deficits (AHOD, g m Ϫ2 d Ϫ1), are calculated on the basis of weekly DO profiles of 1-m resolution and estimates of coincident inputs of DO from overlying layers driven by vertical mixing. Vertical mixing inputs of DO are important in this system, representing from 15% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 48 publications
(124 reference statements)
1
55
0
1
Order By: Relevance
“…This can be a substantial fraction of total AHM, especially in lakes with a small hypolimnion volume. Matthews and Effler (2006) showed the importance of F red for sediment O 2 demand in Onondaga Lake. Further, F red was responsible for up to 42 and 86 % of the total AHM in the Pfäffikersee and Türlersee (Switzerland), respectively, where NH + 4 and CH 4 fluxes represented up to 90 % of F red , while Fe(II) and Mn(II) fluxes played only a minor role (Matzinger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This can be a substantial fraction of total AHM, especially in lakes with a small hypolimnion volume. Matthews and Effler (2006) showed the importance of F red for sediment O 2 demand in Onondaga Lake. Further, F red was responsible for up to 42 and 86 % of the total AHM in the Pfäffikersee and Türlersee (Switzerland), respectively, where NH + 4 and CH 4 fluxes represented up to 90 % of F red , while Fe(II) and Mn(II) fluxes played only a minor role (Matzinger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Matthews and Effler [22], for example, found that a rapid decrease of hypolimnetic oxygen demand in Onondaga Lake, New York, was driven by a decrease in organic matter loading to the bottom waters.…”
Section: Discussionmentioning
confidence: 99%
“…Increased inputs of domestic and industrial wastes accompanied development of the watershed and led to degradation and loss of uses, including the cold-water fishery (late 1800s; Tango and Ringler 1996). Manifestations of severe cultural eutrophication included: (1) high concentrations of phytoplankton biomass, with occurrences of blooms of nuisance cyanobacteria (Matthews et al 2001); (2) low water clarity (Effler et al 2008b); (3) rapid seasonal loss of dissolved oxygen (DO) from the hypolimnion (Matthews and Effler 2006b); (4) accumulation of reduced by-products of anaerobic metabolism (Matthews et al 2008); and (5) severe depletion of DO in the upper waters during fall mixing associated with oxidation of the reduced constituents (Matthews and Effler 2006a).…”
Section: Cultural Eutrophication P Management and Lake Responsesmentioning
confidence: 99%